Liver cancer: expression features of hepatitis B antigens - V. A. Tumanskiy; M. D. Zubko (Zaporozhye State Medical University, 2013)
Introduction. Hepatocellular carcinoma (HCC) is currently the fifth most common malignancy in men and the eighth in women worldwide. According to the latest European Union countries' statistics the incidence of HC cancer is about 8,29 per 100000 accidents, cholangiocellular (CC) cancer - 0,9-1,3 per 100 thousand of population per year[10,14]. Hepatitis B virus (HBV) is the major etiologic factor for the development of HCC [18]. People chronically infected with HBV are 20 times more likely to develop liver cancer than uninfected people [1,22,28]. Many studies have shown the association between Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections and the development of cholangiocarcinoma (CCA) [4,6,9,11,12]. At the same time, the expression features of HBsAg, HBcAg in HCC and CCA have not been studied clearly yet. Aim of investigation: to study the expression features of hepatitis B antigens in tumor tissue from patients with hepatocellular carcinoma and cholangiocarcinoma. Materials and methods. The complex pathomorphological research was performed using liver biopsies of 87 patients aged from 33 up to 83 years, where 50 (57,47%) of them had HCC carcinoma and 37 (42,53%) had cholangiocellular cancer. 15 patients among examined 87 ones were ill with chronic viral hepatitis (11 were ill with HCV, 3 - HBV B, 1 - HBV + HCV) before, 72 cancer patients, corresponding to the clinical data, never had this one in their past medical history. The localization of hepatitis B surface antigen (HBsAg) and core antigen (HBcAg) was investigated by an indirect immunoperoxidase method in formalin-fixed, paraffin-embedded liver specimens obtained from 50 (57,47%) patients with hepatocellular carcinoma and 37 (42,53%) patients with cholangiocarcinoma. using antibodies Rb a-Hu Primary Hepatitis B Virus Core Antigen (HBcAg) and Mo a-Hu Primary Hepatitis B Virus Surface Antigen (HBsAg), Сlone 3E7, and visualization system DAKO EnVision+ with diaminobenzidine. Liver biopsies of patients without any liver disease were used as samples for test-control. Results. The diffuse granular cytoplasmic and nuclear expression of HbcAg of varied intensity was revealed in 100% of patients with hepatocellular carcinoma in differentiated and poorly differentiated tumor cells, in 82,0% varied intensity of HbsAg expression in the tumor cells' cytoplasm was found. There is strong direct correlation between the levels of tumor cells' HBcAg and HBsAg expression (Pearson coefficient is r=+0,87) in the patients with hepatocellular carcinoma. The cytoplasmic and nuclear expression of HbcAg in the tumor cells was revealed in 72,97% of patients, and cytoplasmic HbsAg expression placed in the liver tumor tissue was determined in 43,25% among 37 diseased persons. Expression of HBcAg and HBsAg was detected in the tumor cholangiocytes in undifferentiated tumor cells and sporadic fibroblast cells. Patients ill with HC carcinoma have strong direct correlation between the level of expression of tumor cells' HBcAg and HBsAg (Pearson coefficient is r=+0,82). It's assumed, that the HBcAg and HBSAg expression in HCC and CCA cells can be explained by the liver stem cells infection at the stage of differentiation of progenitor cells into new generations of cholangiocytes and hepatocytes on the eve of cancer development in patients with latent HBV infection. Conclusions. The high level expression of HBsAg was detected in liver specimens obtained from 55,17% patients with hepatocellular carcinoma and 27,73% patients with cholangiocarcinoma as well as high level expression of HbcAg in liver specimens obtained from 74,0% patients with hepatocellular carcinoma and 40,22% patients with cholangiocarcinoma. The results from our study demonstrate the principal role of hepatitis B in the development of hepatocellular carcinoma and cholangiocarcinoma.